2008
DOI: 10.1143/jjap.47.3851
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Constants of Single-Crystal Rare-Earth Bismuth Iron Garnet Films

Abstract: Complete sets of elastic constants of rare-earth bismuth iron garnet (111) films containing Pb were determined by resonantultrasound spectroscopy. Resonant-ultrasound spectroscopy can be used to determine all independent elastic constants from one specimen by measuring the resonance frequencies of free vibrations. For accurate measurement of the resonance frequencies, we used a tripod transducer, and the vibration modes of each resonance frequency were identified by laser-Doppler interferometry. Rare-earth bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…[ 11 ] A significant difference in c 44 values for PLD‐grown garnets appears unlikely, because a study on LPE‐grown Bi:YIG showed c 44 very close to bulk. [ 42 ] One possibility is the existence of growth‐induced anisotropy from cation ordering on the iron sublattice. Previous work on iron‐deficient YIG has shown that vacancies preferentially form on the octahedral sublattice during PLD growth, giving rise to an additional growth induced anisotropy.…”
Section: Vsm Characterization and Anisotropy Analysismentioning
confidence: 99%
“…[ 11 ] A significant difference in c 44 values for PLD‐grown garnets appears unlikely, because a study on LPE‐grown Bi:YIG showed c 44 very close to bulk. [ 42 ] One possibility is the existence of growth‐induced anisotropy from cation ordering on the iron sublattice. Previous work on iron‐deficient YIG has shown that vacancies preferentially form on the octahedral sublattice during PLD growth, giving rise to an additional growth induced anisotropy.…”
Section: Vsm Characterization and Anisotropy Analysismentioning
confidence: 99%
“…[ 40–43 ] The complex transmission parameter S 21 was measured at a fixed frequency while the external perpendicular magnetic field was swept, [ 40 ] as shown in Figure a,b. The resonance field for the films was fitted to the Kittel equation for perpendicular geometry to extract the effective magnetization M eff and the Landé g‐factor, [ 44 ] as shown in Figure 5c for one film as an example. Here: Hresbadbreak=2πnormalf||γμogoodbreak+Meff$$\begin{equation}{H}_{{\mathrm{res}}} = \frac{{2\pi {\mathrm{f}}}}{{\left| \gamma \right|{\mu }_o}} + {M}_{{\mathrm{eff}}}\end{equation}$$where H res is the resonance field, f is the excitation frequency, and γ is the gyromagnetic ratio ( gµ B )/ h , where µ B is the Bohr magneton and ħ is the reduced Planck constant.…”
Section: Resultsmentioning
confidence: 99%
“…To extract the damping of the BiYIG thin films, their dynamic magnetic properties were studied with broadband perpendicular FMR spectroscopy based on the vector network analyzer (VNA) technique in the 10-40 GHz range. [40][41][42][43] The complex transmission parameter S 21 was measured at a fixed frequency while the external perpendicular magnetic field was swept, [40] as shown in The resonance field for the films was fitted to the Kittel equation for perpendicular geometry to extract the effective magnetization M eff and the Landé g-factor, [44] as shown in Figure 5c for one film as an example. Here:…”
Section: Ferromagnetic Resonance Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the research related to ultrasonic nonlinearity has been valuable. 82 Ultrasonic properties of materials, phonon physics, acousto-optics Properties of materials viscosity [20][21][22][23][24][25][26][27] elasticity [28][29][30][31][32][33][34][35][36][37][38] Wave propagation [39][40][41][42][43] Waveguides 44) Piezoelectric materials [45][46][47][48][49][50][51][52][53][54] Quantum acoustics 55) Acousto-optics 30,31,34,39,40,[56][57][58][59][60][61][62][63]…”
Section: Transmittermentioning
confidence: 99%